Pilot Study of the Adaptation of an Alcohol, Tobacco, and Illicit Drug Use Intervention for Vulnerable Urban Young Adults - Ferguson, Tekeda F.; Beauchamp, Alaina; Rosen, Erika M.; Ray, A. Nicole; Theall, Katherine P.; Gilpin, Nicholas W.; Molina, Patricia E.; Edwards, Scott (Frontiers in Public Health, 2020)
Objectives: There is limited information about the applicability and effectiveness of tobacco and illicit drug use interventions in urban and racial/ethnic minority youth, a population with great need for prevention of alcohol and drug use. We pilot-tested the feasibility of a behavioral intervention to reduce alcohol, tobacco, and illicit drug use among urban young adults in New Orleans, Louisiana. Study Design: The 12-week intervention pilot project was developed to be implemented at a community-based social service organization that provides educational, juvenile justice-related case management, and mentoring services to youth with substance use and incarceration histories. Methods: One-hour intervention sessions included interactive discussions and lesson reviews guided by a health educator and peer facilitators. Recruitment was done by case managers. Thirty African American young adults aged 16–21 years participated between January 2016 and July 2017. Results: We were able to adapt the 14-session intervention to a 12-session, weekly curriculum that was well-received by the target population. Average rating for each session was 9.5 ± 0.3 (scale 0–10). Youth were willing to engage in the program, but retention was low. Rates of alcohol and drug use were significantly higher within our pilot population than national estimates. We found no significant decreases in self-reported alcohol, tobacco, or illicit drug use after participation in the intervention. Conclusion: Results emphasize the need to devote additional educational resources to intervention and retention factors for vulnerable youth. Individuals often experiment with drugs during adolescence; thus, this period represents a prime opportunity for education and intervention.